An introductory course in philosophy of medicine. Issue 1 (10th June 2004) - Rudnick, A
Abstract : Philosophy of medicine, narrowly defined as ontology and epistemology of medicine, is a well developed research field, yet education in this field is less well developed. The aim of this paper is to present an educational development in philosophy of medicine—an introductory course in philosophy of medicine. Central features of the course are described. Participants (medical undergraduate students) scored high on average. The conclusion is that further such educational ventures in philosophy of medicine should be developed and implemented.